Singapore General Election 2015: Opposition’s Need to Re-Strategise - Saleena Saleem (2015)
The PAP’s nearly 10 percent point increase in popular vote from the 2011 general election is as much a reflection of the electorate’s rousing endorsement of the existing government as it is of the opposition’s continued failure to speak to the majority of the people.